TRAINING ON PREPARING FINANCIAL REPORTS FOR PKK WOMEN'S GROUPIN LINGGARSARI VILLAGE - Dhea Imroatul Fatihah (Jurnal Pengabdian Masyarakat, 2024)
With the provision of knowledge and training to PKK mothers regarding the preparation offinancial reports, it is hoped that they will be able to overcome obstacles and problems in theprocess of preparing good and correct finances. In its implementation, it is carried out in severalstages, starting from the planning and preparation stage, followed by the implementation stage,completed and ending with the evaluation stage. The results of the implementation of this activityshowed that prior to the implementation of the activities the PKK mothers in Linggarsari villagedid not understand financial reports, but after the implementation of the activities the PKKmothers in Linggarsai village had understood and were able to improve the abilities of PKKmothers in making PKK financial reports personally and in groups